Análise da aderência ao tratamento com imatinib na leucemia mielóide crônica: um estudo retrospectivo em um hospital da Amazônia brasileira - ANDRADE, Alan Rodrigues (2020)
Background: There has been a revolution in the treatment of Chronic Myeloid Leukemia since imatinib's introduction. However, patient adherence has a great impact on the response obtained with medical treatment. This study's objective was to analyze the drug adherence and the factors that influenced it in patients with Chronic Myeloid Leukemia in a referral hospital in the Brazilian Amazon. Method: Retrospective study including 120 patients with Chronic Myeloid Leukemia from January 2002 to December 2014. The adherence was estimated by the Proportion of Days Covered, and the persistence by Kaplan-Meier analysis. The data was analyzed in Epi Info 7® software and the relationship between continuous and categorical variables was analyzed by Mann-Whitney’s U Test and Fisher's exact, respectively. A p-value lower than 0.05 was considered significant. Results: Twenty-seven patients (22.5%) were considered non-adherent. There has been irregular medication use and disinterest in the treatment in 20.83% (n=25) of which 13 were considered non-adherent (p<0.001). 26.67% (n=32) abandoned the treatment for a period. Of those, 56.25% (n=18) were non-adherent (p<0.001). Distance to the hospital, lack of medication and side-effects were all non-significant to low adherence. At the end of a 360-days-follow-up, 44.16% (n=53) of patients presented a break in persistence, which average was 255 days. Conclusion: The adherence found in this study was similar to that found in others of its kind. The only factors that negatively influenced the adherence were disinterest and abandon of treatment, which can reflect the need to individually educate Chronic Myeloid Leukemia suffering patients.